The Influence of Store Image, Service Quality, Private Label Brand Image, Perceived Risk, and Price Consciousness on Purchase Intention - Meta Andriani (Indonesia Banking School, 2016)
Previous study found supporting evidence of several factors affecting purchase intention in retail environment. However, there is still few that focus on the private label brand (PLB) despite of the importance of the products for the convinience store business. This study aims to find the direct effects of store image and service quality on brand image and purchase intention for a private label brand (PLB) in the context of convinience store. In addition, it also aims to confirm the factors that directly influence purchase intention of consumers. Two hundred and seven respondents were investigated using nonprobability sampling technique (purposive sampling). The analyses emploted Structural Equation Modelling techniques and results indicate that store the image and private label brand image has a direct positive impact on purchase intention. The findings also confirmed that service quality has a direct positive effect on private label brand (PLB) image. Surprisingly, service quality has no direct influence on purchase intention, but have indirect influence through private label brand (PLB) image.